2022
DOI: 10.3390/brainsci12111466
|View full text |Cite
|
Sign up to set email alerts
|

Vortioxetine Improves Depressive Symptoms and Cognition in Parkinson’s Disease Patients with Major Depression: An Open-Label Prospective Study

Abstract: Depression is frequent in Parkinson’s disease (PD) patients, but the evidence for many antidepressant agents to treat it in PD is insufficient. The aim of the present prospective open-label single-arm study (VOPARK, an open-label study of the effectiveness and safety of VOrtioxetine in PARKinson´s disease patients with depression) was to analyze the effectiveness of vortioxetine on depressive symptoms in PD patients with major depression. The primary efficacy outcome was the change from baseline (VB) at the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…A recent single-arm open-label study, the VOPARK study, evaluated vortioxetine as a therapy for depressive symptoms suffered by PD patients who concurrently met diagnostic criteria for major depressive disorder. The investigators found that as well as improving mood, there was a significant effect on apathy as measured using the apathy scale [26]. While we could not find any further studies that evaluate the effect of vortioxetine on apathy, one trial found a significant short-term effect on anhedonia.…”
Section: Vortioxetinementioning
confidence: 66%
See 1 more Smart Citation
“…A recent single-arm open-label study, the VOPARK study, evaluated vortioxetine as a therapy for depressive symptoms suffered by PD patients who concurrently met diagnostic criteria for major depressive disorder. The investigators found that as well as improving mood, there was a significant effect on apathy as measured using the apathy scale [26]. While we could not find any further studies that evaluate the effect of vortioxetine on apathy, one trial found a significant short-term effect on anhedonia.…”
Section: Vortioxetinementioning
confidence: 66%
“…The most extensively researched and commonly prescribed pharmacological treatments for apathy are dopaminergic agents (e.g., rotigotine) and cholinesterase inhibitors (e.g., rivastigmine) [1,25]. However, the list of trialled therapies continues to grow, and recently published studies have examined vortioxetine [26] and the experimental compound pirepemat [27]. Non-pharmacological therapies that have shown specific benefits for apathy in PD include exercise therapy and mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…Vortioxetine has been shown to be well-tolerated and efficacious in patients with MDD and comorbid physical conditions, such as cardiovascular disease, diabetes mellitus, Parkinson’s disease [ 53 ] and, to a lesser extent, chronic obstructive pulmonary disorders (COPD) [ 54 ]. Notably, vortioxetine’s effectiveness and tolerability extend to older populations, who often deal with multiple comorbidities and polypharmacy [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…These articles report encouraging results in the treatment of negative, cognitive and affective symptoms of schizophrenia [108][109][110], along with preliminary effectiveness in bipolar depression [111], burning mouth syndrome [112], postmenopausal depression [113], and panic disorder [114]. A further group of studies (n = 5) demonstrated that vortioxetine treatment is associated with affective and cognitive symptoms amelioration in patients with neurological conditions, including neurocognitive decline [115][116][117], Parkinson's disease [118], and post-stroke depression [119]. Interestingly, three studies report data suggesting that vortioxetine could be an effective strategy to reduce SSRI-induced emotional blunting [120][121][122].…”
Section: Analytical Observational Studiesmentioning
confidence: 98%